Bimetallic CoMo Nanoparticles Supported over Carbon-Zeolite Composites as Dibenzothiophene Hydrodesulfurization Catalyst - Zahra Mohammadian; Mohammad Hasan Peyrovi; Nastaran Parsafard (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Cobalt molybdenum catalysts supported on novel activated carbon-HZSM-5 composites with different mass ratios were prepared by wet-impregnation method and pre-sulfided by CS2. Characterization of these catalysts was done using X-ray powder diffraction, Fourier transform infrared spectroscopy, N2 adsorption-desorption, and scanning electron microscope analytics. Their activity for the hydrodesulfurization reaction of dibenzothiophene was investigated at atmospheric pressure in the temperature range of 250–400 °C using the fixed-bed reactor with 0.5 g of each powder and pre-sulfided with CS2. The highest conversion of dibenzothiophene at the temperature range of 300–400 °C was obtained for the CoMo/activated carbon-HZSM-5(1:1) catalyst. The best selectivity for cyclohexylbenzene, which is the dominant product according to gas chromatography results, was obtained at all temperatures using CoMo/activated carbon-HZSM-5(3:1) catalyst. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).